Mechanism and application of copper-based nanomedicines in activating tumor immunity through oxidative stress modulation - Xia, Cong; Luo, Zirun; Feng, Zhen; Zhang, Qianshi; Xia, Chenglai (Frontiers in Pharmacology, 2025)
Immunotherapy stands as a powerful weapon against tumors. However, tumor cells evade recognition and attack by the immune system through various mechanisms, achieving immune escape and exhibiting resistance to immunotherapy. Metalloimmunotherapy, as an emerging paradigm for immunotherapy, offers the potential to effectively overcome the limitations of current tumor immunotherapies. Nevertheless, developing highly efficient and specific metal-based agents for regulating the tumor immune system remains a significant challenge. The modulation of oxidative stress in the tumor microenvironment (TME) by metals presents novel breakthroughs for metalloimmunotherapy, particularly in enhancing immune responses, optimizing immune cell function, and reprogramming the immunosuppressive TME. Copper, a transition metal closely associated with tumor development, acts as an immune activator to enhance immune responses through oxidative stress. Benefiting from advances in nanomaterials, copper-based nanomedicines have demonstrated significant potential in improving the efficacy of cancer immunotherapy by modulating oxidative stress via Fenton-like reactions and enzymatic catalytic activities. Therefore, summarizing recent advances in copper-based nanomedicine activating tumor immunity through oxidative stress modulation provides new insights and drives progress for metalloimmunology. This review outlines strategies utilizing oxidative stress modulated by copper-based nanomedicines to induce or enhance immunotherapy through multiple forms of regulated cell death (RCD), drug co-delivery approaches, and versatile combination therapies. Finally, we discuss current challenges and offer perspectives on copper-based nanomedicines in tumor immunotherapy. Our review aims to elucidate the potential of copper-based nanomedicines in tumor immunology, providing insights for the future development of tumor immunotherapies based on metal and redox biology.